Standardization of The Scale of Ethnocultural Empathy in Central Indonesia Region (Bali, Kalimantan and Sulawesi) - Fitniwilis, Fitniwilis; Yunus, Ahmad (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2021)
Indonesia is a multi-cultural country and has a plurality in many dimensions. This pluralistic culture is a nation's wealth capital in understanding and interacting with other nations. Current developments have led us to wider interactions across national borders where the relationship involves intercultural aspects. However, building and fostering ethnocultural empathy is an accumulative and continuous process and requires consistency over a long period of time. The most important first process is that we need to analyze the state of cultural empathy in society. This exploration, of course, requires a valid and reliable measuring instrument. As a challenge, we don't have limited instruments to explore this yet. In developing the instrument, the vast territory of Indonesia requires us to research in several periods to get maximum results. In this study, the Scale of Ethnocultural Empathy will be adapted and developed by Wang et al. and tested its validity and reliability in the central region of Indonesia. The number of items tested was 59 on 399 people, consisting of 18 males and 381 females. As for the distribution of the tribes living on Kalimantan, Bali, and Sulawesi, 24% came from the Javanese, and 44.86% of the total population came from the Makasarese, Bugis, Balinese, Ambonese, Minahasa, Dayak, and Kalimantan Malays. The study results showed that the scale of cultural empathy (The Scale of Ethnocultural Empathy / SEE) as a result of adaptation and development of 59 items was declared valid as many as 55 items and 4 items dropped. The results of the study also showed that who selected the scale of cultural empathy (The Scale of Ethnocultural Empathy / SEE) as many as 55 valid items, 58 items that met the item discriminatory value with riX 0.30 in the item discrepancy test stage, thus remaining 55 items based on the validity and item discrepancy. The results of the study also show that the scale of cultural empathy (The Scale ofEthnoculturall Empathy / SEE) as many as 55 items that meet the value of item discriminating power and validity was tested for reliability and obtained a Cronbach's Alpha score of 0.797 so that the instrument with 55 items can be accepted as a scale with reliability. Very high.